Leaching of Imidazolinones in Irrigation Systems in Rice Cultivation: Sprinkling and Flooding - HELGUEIRA,D.B. (2019)
ABSTRACT: Herbicides of the imidazolinone group have been used in irrigated rice and presented a long persistence in the soil, especially in floodplain areas with a low drainage, and could cause environmental contamination. This study aims to evaluate the leaching and residual of herbicides belonging to the imidazolinone group in sprinkler and flood irrigation systems. The experiment was carried out under greenhouse conditions, with the application of the herbicides imazethapyr, imazethapyr + imazapic, and imazapyr + imazapic in soil irrigated by flooding and sprinkling. Subsequently, the soil was collected from the layers of 0-5, 5-10, 10-15, 15-20, and 20-25 cm and packed in 500 mL capacity plastic pots in order to sow tomato as a bioindicator plant of the presence of the herbicides belonging to the imidazolinones. Phytotoxicity, length, and shoot dry matter mass of tomato plants were evaluated at 10 and 20 days after emergence. The herbicides of the imidazolinone chemical group presented a high potential for leaching and persistence with effects for more than 180 days after application. Based on the symptoms presented by the sensitive crop, the degradation of imazethapyr, imazethapyr + imazapic, and imazapyr + imazapic in the 0-15 cm layers was higher in soil with sprinkler irrigation when compared to flood irrigation. Thus, non-flooded soils present a greater capacity to degrade the herbicides belonging to the imidazolinone chemical group.